THU0294 Regulatory T cells/TH17 balance in the pathogenesis of pediatric behçet disease. (23rd January 2014) - Tran, T.-A.; Hubert, A.; Letierce, A.; Terrier, B.; Geri, G.; Saadoun, D.; Kone-Paut, I.; Rosenzwajg, M.
Abstract : Background: Behçet disease (BD) is an idiopathic systemic inflammatory disorder of unknown origin characterizedby recurrent attacks involving the muco-cutaneous, ocular, intestinal, vascular and nervous systems. In adult, it has been shown that Th17 and CD4+FoxP3 regulatory T cells (Tregs) were involved in the pathogenesis of the disease. The promotion of Th17 responses and the suppression of Tregs were induced by IL-21 production (1). Objectives: To determine the nature of T cells driving inflammatory lesions in BD and more precisely the role of regulatory T lymphocytes (Tregs)/Th17 balance in the pathogenesis of BD in children. Methods: Patients with active BD (n=24) and BD patients in remission (n=12) were compared to aged matched healthy subjects (n=25). Percentage and phenotype of Treg (CD4 + CD25 hi CD 127-/lo Foxp3 + ) as well as Th1, Th17/Treg functions after polyclonal (OKT3/IL-2) or antigen specific stimulation (Streptococcus sanguis KTH-1 peptides: BES-1229-243, BES-1373-385, Brn-3b or HSP-60) were assessed by flow cytometry. Serum cytokines were measured by Luminex technology. We compared the 3 groups of subjects by using the Wilcoxon-Rank-signed test. Values were expressed as mean and median. Results: In active and inactive BD patients, Treg levels and other functional Treg markers (GITR, LAP, CD152, HLA-DR) were similar to healthy control in peripheral blood. However, IL-6 was increased in serum and the percentage of IL-17 production CD4 + T cells after polyclonal activation was significantly higher in active BD patients compared to controls (5.3±2 vs 2.5±1.47, p=0.043). There was no significant difference in the percentage of IL-21 production CD4 + T cells between the different groups of subjects. Th1 (IFN-γ secreting cells) CD4 + responses analysis to streptococcal antigens, potentially responsible in BD flare, were similar in BD patients and control subjects. However, Th17 (IL-17 secreting cells) CD4 + responses to specific stimulations were significantly higher in active BD patients compared to controls. When Tregs were removed from total T cells, specific T cell responses were markedly increased in BD patients compared to controls. Conclusions: Tregs number is normal in Pediatric BD patients and the disease is characterized by a Th17 polarization. By contrast to adult BD, IL-21 is not inscreased in BD children. BD flare in children seems to be associated with specific streptococcal antigens T cell response, which is characterized by strong Th17 responses. Despite, the presence of functionally active Tregs, the effector response is not sufficiently counter-balanced to prevent BD flare attacks. References: Geri G, Terrier B, Rosenzwajg M, Wechsler B, Touzot M, Seilhean D, Tran TA, Bodaghi B, Musset L, Klatzmann D, Cacoub P, Saadoun D. Critical role of IL-21 in modulating Th17 and regulatory T cells in Behçet's disease. J Aller Clin Immunol 2011 Sep;128(3):655-64. Disclosure of Interest: None Declared